Tibial Plateau Fractures: A Retrospective Analysis of Treatment Outcomes and the Role of Post-Traumatic Knee Joint Instability - Syvak Андрій; Kalashnikov Андрій; Litun Юрій (Psychosomatic Medicine and General Practice, 2025)
Relevance. Fractures of the proximal tibia (PTF) account for 2–5% of all fractures and are often complicated by knee joint instability, leading to disability. Materials and Methods. A total of 87 cases treated between 2010 and 2022 were analyzed. Clinical, radiological (X-ray, CT), and statistical methods were used. Fracture classification was based on the Schatzker system. Results. The most common fracture types were II (n=20), V (n=18), and III (n=15). Surgical treatment was applied in 91.3% of cases. A “good” functional outcome was achieved in 50% of patients, “satisfactory” in 30%, and “poor” in 20%. The main cause of poor outcomes was knee joint instability (25%). MRI and ultrasound were rarely used for diagnostics (1% and 7%, respectively), though they are essential for identifying soft tissue injuries of the knee joint. Conclusion. Post-traumatic knee joint instability is a clinical issue that requires targeted diagnostics and treatment.